QuickBooks 2007 finance software for small business (McGraw-Hill, 2007)
Get started using QuickBooks 2007 right away--the QuickSteps way. Color screenshots and clear instructions show you how to use all the new and improved features available in this powerful small business financial software. Follow along and learn to customize QuickBooks for your business, set up accounts, handle bookkeeping,process invoices, manage payroll, and much more. Plus, it's easy to flip straight to the information you need using the color-coded tabs. Get the book that gets you started using QuickBooks 2007 in no time.